2018
DOI: 10.1177/0886260518774304
|View full text |Cite
|
Sign up to set email alerts
|

Motives, Offending Behavior, and Gender Differences in Murder Perpetrators With or Without Psychosis

Abstract: Little is known whether differences exist in motivation and reactive/instrumental offense behaviors between murder offenders with and without psychotic disorder. To contribute to better prevention strategies, the aim of this study was to investigate offense characteristics in murder offenders with a psychotic, nonpsychotic or no psychiatric diagnosis, and whether these factors differ according to sex. This data study examined the population of murder offenders between 1997 and 2005 ( N = 435) in Victoria, Aust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…When the motivational matrix is psychotic, the homicide is more likely to be intrafamilial (Richard-Devantoy et al, 2016), as previously also reported by others (Hachtel et al, 2018). In those cases, the crimes often took place in the victim's home.…”
Section: Discussionsupporting
confidence: 67%
“…When the motivational matrix is psychotic, the homicide is more likely to be intrafamilial (Richard-Devantoy et al, 2016), as previously also reported by others (Hachtel et al, 2018). In those cases, the crimes often took place in the victim's home.…”
Section: Discussionsupporting
confidence: 67%
“…The relationship between major psychiatric disorders and homicide has been much debated. Although it is known that the vast majority of violent acts are committed by subjects without any history of psychiatric disorder (1), some research suggests that there is a correlation between the psychotic dimension and homicide (2‐8). Several studies showed that among those patients who suffered from schizophrenia (9‐11), also those who showed cognitive impairment or executive dysfunction, were at higher risk of committing violent acts (12), including homicide.…”
mentioning
confidence: 99%
“…Homicide with a psychotic motive has some unique characteristics (5,7,14,15), even though the subject’s abilities to plan an antisocial act and to execute goal‐directed behavior do not exclude a diagnosis of schizophrenia (5). In these cases, the motive for murder is often revenge, triggered by persecutory (16) delusions (17).…”
mentioning
confidence: 99%
See 2 more Smart Citations